Nitrous oxide misuse reported to two United States data systems during 2000–2019. Issue 1 (1st December 2020) - Forrester, Mathias B.
Abstract: Background: Nitrous oxide may be misused due to its euphoric, dissociative, and hallucinogenic effects. Nitrous oxide misuse has been reported to be increasing. Objective: The objective of this study is to describe nitrous oxide misuse reported to two United States (US) data systems. Methods: Cases were nitrous oxide misuse during 2000-2019 reported to the National Electronic Injury Surveillance System (NEISS), which collects data on consumer product-related injuries treated in US emergency departments (EDs), and the Food and Drug Administration Adverse Event Reporting System (FAERS), which collects reports of adverse events involving drugs and other biologic products. The distribution of cases was determined for selected variables. Results: Of the 26 NEISS cases, the mean annual number of cases was 0.5 (range 0-2) during 2000-2013 and 3.2 (range 1-5) during 2014-2019. The patients were 92.3% age 13-39 years and 76.9% male. The patient was treated or examined and released from the ED in 84.6% of the cases. Of the 128 FAERS cases, the mean annual number of cases was 0.4 (range 0-2) during 2000-2013 and 20.3 (range 10-34) during 2014-2019. The patients were 90.2%% age 13-39 years and 77.3% male. A serious classification was assigned to 97.7% of the cases. Conclusions: Nitrous oxide misuse reported to NEISS and FAERS both increased during 2000-2019, particularly after 2013. The majority of patients were age 13-39 years and male. Most NEISS patients were treated or examined and released from the ED.